REFLECTIONS ON UNDERGROUND WATER SUPPLY STRUCTURES IN THE DISHAN-KALA AREA OF KHIVA (TAMADDUN NURI JURNALI, 2024)
This article presents the results of archaeological research of underground water supply structures discovered in the eastern part of the territory of Dishan-kala. The design of underground water supply structures and similar structures studied in Central Asia are analyzed. Based on the results of the study, opinions are expressed and conclusions are made regarding underground water supply structures associated with the infrastructure of the city of Khiva in the XVIIIth-XIXth centuries.